Voice Quality Outcomes After Transoral CO2 Laser Cordectomy: A Longitudinal Prospective Study. (29th January 2023) - Lechien, Jerome R.; Crevier‐Buchman, Lise; Circiu, Marta P.; De Mones, Erwan; de Pemille, Grégoire Vialatte; Julien‐Laferriere, Aude; Saussez, Sven; Baudouin, Robin; Remacle, Marc; Hans, Stephane
Abstract: Objective: To evaluate the evolution of voice quality in patients after type I‐VI transoral CO2 laser cordectomy (TLC) by using validated voice outcome measures over a 12‐month period. Study Design: Prospective uncontrolled study. Setting: Monocenter study. Methods: Patients with laryngeal carcinoma who were eligible for type I‐IV TLC were prospectively recruited from a tertiary medical center. The following outcomes were assessed throughout the 12‐month posttreatment period: Voice Handicap Index (VHI), GRBAS (grade of dysphonia, roughness, breathiness, asthenia, strain), maximal phonation time, fundamental frequency (F0), F0 standard deviation, percentage jitter, percentage shimmer, noise‐to‐harmonic ratio, and speech fluency. Analyses were performed considering 2 groups of cordectomies: type I‐III vs IV‐VI. Results: A total of 131 patients completed the evaluations, totaling 76 type I‐III and 55 type IV‐VI cordectomies. In type IV‐VI, breathiness and maximal phonation time significantly worsened from pretreatment to 1 month posttreatment ( P < .05). In the type I‐III cordectomy group, VHI, shimmer, roughness, breathiness, and strain significantly improved from pretreatment to 3 months posttreatment, while VHI, F0 standard deviation, shimmer, jitter, grade of dysphonia, roughness, breathiness, and strain improved from baseline to 6 months. Assessments at 12 months posttreatment revealed significant improvements for VHI, shimmer, jitter, noise‐to‐harmonic ratio, grade of dysphonia, roughness, breathiness, and strain. In the type IV‐VI group, VHI significantly improved from baseline to 3, 6, and 12 months posttreatment. Strain improved at 6 and 12 months while roughness improved from baseline to 12 months. Maximal phonation time significantly worsened over the 12‐month evaluation period. Conclusion: The effect of TLC on voice quality depends on its type. VHI was identified as the most indicative tool of voice changes irrespective of TLC type.